2017
DOI: 10.1007/s00259-017-3647-y
|View full text |Cite
|
Sign up to set email alerts
|

18F-FDG PET-CT imaging versus bone marrow biopsy in pediatric Hodgkin’s lymphoma: a quantitative assessment of marrow uptake and novel insights into clinical implications of marrow involvement

Abstract: F-FDG PET-CT imaging is more sensitive than BMB for BMI detection in pHL staging. BMB should be limited to those with normal marrow uptake in the presence of poor risk factors or those with diffusely increased uptake to exclude marrow involvement in the background of reactive marrow.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
18
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 22 publications
1
18
0
Order By: Relevance
“…Our results showed a high sensitivity (100%) of PET–CT when assessing marrow disease in pediatric patients with certain solid tumors and lymphomas. Akin to our study, larger retrospective reviews assessing PET–CT sensitivity in patients with HL have demonstrated similar results ultimately recommending BMBs to those with normal marrow uptake in the presence of poor risk factors or those with diffusely increased uptake to exclude marrow involvement in the background of reactive marrow . Furthermore, PET–CT detected all the infiltrations identified by BMBs.…”
Section: Discussionsupporting
confidence: 72%
See 1 more Smart Citation
“…Our results showed a high sensitivity (100%) of PET–CT when assessing marrow disease in pediatric patients with certain solid tumors and lymphomas. Akin to our study, larger retrospective reviews assessing PET–CT sensitivity in patients with HL have demonstrated similar results ultimately recommending BMBs to those with normal marrow uptake in the presence of poor risk factors or those with diffusely increased uptake to exclude marrow involvement in the background of reactive marrow . Furthermore, PET–CT detected all the infiltrations identified by BMBs.…”
Section: Discussionsupporting
confidence: 72%
“…Akin to our study, larger retrospective reviews assessing PET-CT sensitivity in patients with HL have demonstrated similar results ultimately recommending BMBs to those with normal marrow uptake in the presence of poor risk factors or those with diffusely increased uptake to exclude marrow involvement in the background of reactive marrow. 7,8 Furthermore, PET-CT detected all the infiltrations identified by BMBs. An important advantage of this method over BMB is its ability to assess all bone marrow sites at once and reveal unanticipated bone marrow infiltration at areas not usually biopsied, such as the femoral head and tibia in a patient with lymphoma ( Fig.…”
Section: Discussionmentioning
confidence: 94%
“…Iliac crest bone marrow biopsy (BMB) has been traditionally used for marrow assessment. It is obtained from the posterior portion of iliac crest, as it is the most easily accessible approach [4].…”
Section: Introductionmentioning
confidence: 99%
“…Since asymmetry in 18 F‐FDG uptake was a key criterion to prompt further structured analysis, such cases could be missed. However, as frequently published, for example, for skeletal involvement, HL lesions are regularly of focal and not diffuse appearance in 18 F‐FDG‐PET 21,22 . Furthermore, five of these six patients did not show 18 F‐FDG‐PET response compatible with lymphoma manifestation when reanalyzed after two cycles of chemotherapy.…”
Section: Discussionmentioning
confidence: 53%